A comparative analysis on the financial performance between Takaful and conventional insurance companies in Malaysia - Nor Aishah, Hamdan (2018)
This study attempts to measure the financial performance between Takaful and conventional insurance companies in Malaysia in ten years from year 2007 to 2016. Based on this study, researcher identify whether any differences exist between financial performance between Takaful and conventional insurance companies in Malaysia by using the financial ratio. To complete this task, researcher used financial ratio analysis method to draw the overview about financial performance between Takaful and conventional insurance companies in term of solvency, liquidity, profitability, underwriting performance and operating efficiency. To test the hypothesis of this study, researcher used descriptive analysis and T-test to compare the financial performance between Takaful and conventional insurance companies. These analyses help to see the financial performance for both institutions due in increasing the insurance industry in Malaysia. The finding of this study can be useful on the management for Takaful and conventional insurance companies in Malaysia to improve their financial performance based on financial ratio. The finding indicates that Takaful companies are better performed in financial performance compare to conventional insurance companies in Malaysia based on the financial ratio. Takaful companies are performed better in term of solvency ratio, cash ratio (liquidity ratio), profitability ratio (net profit margin and gross profit margin) and operating efficiency ratio which is account receivable turnover and total asset turnover. While, for the conventional insurance companies is liquidity (current ratio and net working capital) and underwriting performance